Funcionalidad familiar y logros de aprendizaje en el área de comunicación en estudiantes del sexto grado de primaria de la Institución Educativa N° 60050, Iquitos 2025 - Velasquez Ramirez, Solange (2025)
The main purpose of this study was to explain the relationship between family functionality and learning achievement in the area of communication in sixth grade students of I.E. N° 60050, Iquitos 2025. Methodologically, a type of basic analysis and non-experimental cross-sectional design was carried out. The research considered a population of 90 students, from which 90 students were selected as a non-probabilistic sample by census. For data collection, the survey technique was used by means of a questionnaire for the family functionality variable, which was validated by experts in the field, in addition to the documentary observation of the qualifying records for the learning achievement variable in the area of communication. The results showed a significant relationship between family functionality and learning achievement in the area of communication in students in the sixth grade of primary school at I.E. N° 60050, Iquitos 2025. The results of the hypothesis testing confirmed the significant relationship between the variables studied. In the general hypothesis, the null hypothesis (H₀), which stated that there was no significant relationship, was rejected, and the alternative hypothesis (H₁), which indicated that there was a significant relationship between family functionality and learning achievement, was approved. Spearman's test values confirmed this relationship with a correlation coefficient of 0.991 (p = 0.000), demonstrating a very high and significant relationship.